INVESTIGATING EFL LEARNERS’ ENGAGEMENT THROUGH DIGITAL STORYTELLING: A CASE STUDY AT ISLAMIC HIGH SCHOOL IN CIAMIS - Diana Lestari; Lilies Youlia Friatin; Dedeh Rohayati (Universitas Galuh, 2022)
This study aimed to investigate students’ activities during digital storytelling lessons and whether digital storytelling affects EFL students’ engagement or not and identify the extent to which the improvement of EFL students’ interest in their learning process by using digital storytelling. The present study implemented a qualitative approach. A case study was applied as a research design. The instruments in this study were observation and interview. The data analysis of this study is based on what the researcher observed; the observation was utilized to generate a description of whether or not students’ engagement in implementing digital storytelling in the classroom was achieved. The researcher transcribed all of the interviews which were recorded to analyze the data from the interviews. In this research, non-random sampling was used to choose the participants. The sample consisted of four participants, which were categorized based on gender. There were 2 male students and 2 female students. The results show that digital storytelling can affect EFL students’ engagement and the researcher found that the application of digital storytelling could increase students' interest in the learning process.